2017
DOI: 10.1002/aic.15748
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of supported Pd–Ir/Al2O3 bimetallic catalysts for 2‐ethylanthraquinone hydrogenation

Abstract: A series of χ wt % Pd‐(1‐χ) wt % Ir (χ = 0.75, 0.50, and 0.25) catalysts supported on γ‐Al2O3 have been prepared by co‐impregnation and calcination‐reduction, and subsequently employed in the hydrogenation of 2‐ethylanthraquinone—a key step in the manufacture of hydrogen peroxide. Detailed studies showed that the size and structure of the bimetallic Pd–Ir particles vary as a function of Pd/Ir ratio. By virtue of its small metal particle size and the strong interaction between Pd and Ir, the 0.75 wt % Pd–0.25 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 67 publications
1
18
0
Order By: Relevance
“…Two iridium states are registered by XPS in our PdIr/C catalysts, similarly to PdIr/TiO 2 [58], PdIr/ Al 2 O 3 [52,53] PdIr/C [30] and PdIr nanoporous aggregates [32]. The lower Ir 4f 7/2 binding energy of 60.8-61.3 eV could be ascribed to the metallic Ir°.…”
Section: Xps Studiesmentioning
confidence: 59%
See 2 more Smart Citations
“…Two iridium states are registered by XPS in our PdIr/C catalysts, similarly to PdIr/TiO 2 [58], PdIr/ Al 2 O 3 [52,53] PdIr/C [30] and PdIr nanoporous aggregates [32]. The lower Ir 4f 7/2 binding energy of 60.8-61.3 eV could be ascribed to the metallic Ir°.…”
Section: Xps Studiesmentioning
confidence: 59%
“…The Ir 4f 7/2 binding energy of metallic iridium Ir°i n the monometallic Ir catalysts was reported in the range of 60. [51] and Ir/γ-Al 2 O 3 [52,53]. These states were observed at 61.1 and 62.8 eV in series of Ir/SiO 2 [54].…”
Section: Xps Studiesmentioning
confidence: 89%
See 1 more Smart Citation
“…Starting from the sixth cycle, the yield of H 2 O 2 decreased from 96.0 % (in the first cycle) to 78 % (in the ninth cycle, on the ninth day). Considering the yield of H 2 O 2 as a characteristic of stability, the PdÀ P/C catalyst is even superior compared with many well-known literary analogues, including Pd monometallic and bimetallic catalysts: 1 wt % Pd/Al 2 O 3 [23] and PdÀ Ir/Al 2 O 3 (0,75 wt % Pd; 0,25 wt % Ir [24] (Table 1)). In terms of H 2 O 2 yield, the initial PdÀ P catalyst nanoparticles (PdÀ P/C) are superior to colloidal Pd/PANI solutions (PANI -polyaniline) (the yield of H 2 O 2 was 85 %).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the support with weak alkalinity possessing high electron density improves the electron density of Pd, which facilitates H 2 activation/dissociation and inhibits the formation of by‐products . In addition, numerous studies have been dedicated to improve the catalytic performance of Pd‐based catalysts by adding promoters, such as Ir, Ni, Co, Ru, La and Zn . Nevertheless, due to the limited catalytic performance of Pd catalysts for 2‐ethylanthraquinone hydrogenation, highly active and stable catalytic materials still need to be developed.…”
Section: Introductionmentioning
confidence: 99%